Anti-inflammatory effects of Streptococcus pneumoniae toxin pneumolysin. (25th February 2016) - Periselneris, Jimstan; Noursadeghi, Mahdad; Brown, Jeremy
Abstract: Background: Streptococcus pneumoniae is the second commonest cause of bacterial mortality worldwide. Interactions of S pneumoniae with alveolar macrophages are important for the protective inflammatory responses during early lung infection. Pneumolysin is a well-recognised virulence factor for S pneumonia ; the toxin has multiple effects on the host immune response that are primarily thought to be proinflammatory. Our aim was to characterise the inflammatory effects of pneumolysin on macrophages. Methods: We used in-vitro culture of primary human monocyte-derived macrophages (MDM) with S pneumoniae and an isogenic mutant lacking pneumolysin. We measured cytokine production (including tumour necrosis factor [TNF] and interleukin 6 [IL6]) at transcriptional and protein level, as well as transcription factor function, to look at mechanisms of interaction between MDM and bacteria. We extended these data with epithelial cell line work and neutrophil transmigration models. Then we used a murine intranasal infection model to assess functional effects in vivo. Findings: Higher mean concentrations of TNF and IL6 were induced from MDM in response to pneumolysin-deficient bacteria than in response to wild-type bacteria (6014 pg/ml [SD 970] vs 2295 [470] and 821 [374] vs 89 [28], respectively). This finding was reflected in TNF mRNA (change in cycle threshold 4·3 vs 2·4) and IL6 mRNA (3·5 vs 0·4). Transcriptome analysis of MDMs after S pneumoniae infection confirmed increased expression of a range of proinflammatory genes, including IL12, IL27, CCR7, IL5, and CCL5, in response to the pneumolysin mutant. The increase in transcription of proinflammatory genes and concentrations of TNF and IL6 in supernatant in response to the pneumolysin-deficient strain were abrogated by inhibition of phagocytosis. In a murine pneumonia model, despite more rapid clearance of the pneumolysin-deficient mutant (1 × 10 4 colony-forming units [CFU]/mL) compared with the wild type strain (1 × 10 5 CFU/mL) from bronchoalveolar lavage fluid (BALF) by 4 h, mean concentrations of TNF were elevated in BALF fluid with the mutant (1336 pg/mL [SD 130] vs 6164 [632]). This increase was associated with more rapid neutrophil influx with the pneumolysin-deficient mutant than with the wild-type strain into BALF seen at 2 h (107 neutrophils per mL [SD 39] vs 3303 [1624]). Blockade of TNF abrogated the differences in clearance between the pneumolysin mutant and wild-type strain. Interpretation: These data indicate an unexpected role for pneumolysin as an initial suppressor of macrophage inflammatory responses, which is dependent on phagocytosis. The early inflammation dampening effects of pneumolysin released within the phagolysosome might be an important contribution to the virulence of S pneumoniae . The inhibition of TNF release allows increased bacterial replication early during the course of infection, and presumably is an evolutionary advantage. Funding: Medical Research Council.